إرادة المریض في العقد الطبي طبقا للتشریع الجزائري مقارنا - باركة إبراهيم (My University, 2017)
The legal protection , whish aims the legislator, to ensure to the patient through the medical contract, between the doctor and the patient, has effects only by respecting the will of this last one. This will is essential il the conclusion of any medical. Consequently , a significant consequences arise in the execution of this contract. The durty of the doctor lies in the explanation known as the obligation of enlightening or informing, on the one hand , and the consent of the patient on the other hand